Presence of trypanosomatids, with emphasis on Leishmania, in Rodentia and Didelphimorphia mammals of a rural settlement in the central Amazon region - Achilles, Genevere Reis (2021)
Fundação de Amparo a Pesquisa do Estado do Amazonas (FAPEAM).